2021
DOI: 10.3389/fnbeh.2021.706660
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Maternal Stress From a Natural Disaster and Hippocampal Volumes: Gene-by-Environment Interactions in Young Adolescents From Project Ice Storm

Abstract: Gene-by-environment interactions influence brain development from conception to adulthood. In particular, the prenatal period is a window of vulnerability for the interplay between environmental and genetic factors to influence brain development. Rodent and human research demonstrates that prenatal maternal stress (PNMS) alters hippocampal volumes. Although PNMS affects hippocampal size on average, similar degrees of PNMS lead to different effects in different individuals. This differential susceptibility to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…In agreement with the findings from numerous earlier studies, our results suggest in utero stress exposure may be associated with a larger amygdala volume ( Buss et al, 2012 ; Wen et al, 2017 ; Acosta et al, 2019 ; Jones et al, 2019 ) and a larger hippocampal volume ( Cao-Lei et al, 2021 ), although less supported. It has been further suggested that prenatal stress exposure appears to accelerate the development of these regions, particularly the amygdala, as a means of allowing more rapid detection of incoming danger and threat ( Lautarescu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the findings from numerous earlier studies, our results suggest in utero stress exposure may be associated with a larger amygdala volume ( Buss et al, 2012 ; Wen et al, 2017 ; Acosta et al, 2019 ; Jones et al, 2019 ) and a larger hippocampal volume ( Cao-Lei et al, 2021 ), although less supported. It has been further suggested that prenatal stress exposure appears to accelerate the development of these regions, particularly the amygdala, as a means of allowing more rapid detection of incoming danger and threat ( Lautarescu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also tested the associations between the severity of PNMS and hippocampal subfield volumes; none of the results survived FDR correction. The results from Project Ice Storm at age 11½ indicated that (1) greater maternal objective hardship was associated with increased right whole hippocampal volume in girls; (2) COMT genotype moderated the association between maternal objective hardship and right whole hippocampal volume in boys; and (3) COMT genotype moderated the association between maternal subjective distress and right whole hippocampal volume in girls ( Cao-Lei et al, 2021 ). Some differences between age 11½ and the current study are that the age 11½ analyses were conducted with whole hippocampal volume only, and that the age 11½ analyses were conducted with boys and girls separately.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus plays a central role in learning and memory ( Wingenfeld and Wolf, 2014 ). Three studies have shown that pre-natal maternal psychological distress ( Lehtola et al, 2020 ; Moog et al, 2021 ) and anxiety ( Wu et al, 2020 ) are associated with decreased whole hippocampal volume in fetuses ( Wu et al, 2020 ) or in neonates ( Lehtola et al, 2020 ; Moog et al, 2021 ); disaster-related PNMS has been associated with increased whole hippocampal volume in adolescents ( Cao-Lei et al, 2021 ), while two other studies have reported no associations between pre-natal maternal cortisol ( Buss et al, 2012 ) or stressful life events ( Marečková et al, 2018 ) and whole hippocampal volume in children ( Buss et al, 2012 ) or in young adults ( Marečková et al, 2018 ). The mixed findings may be attributed to differences in types of stress and offspring age at scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also identified associations between disaster-related prenatal maternal stress and child brain structure. Objective stress later in gestation during the 1998 Quebec Ice Storm was associated with smaller right hippocampus volume and larger amygdala volume in 11-year old females, and amygdala volume mediated the association between prenatal stress and child externalizing behaviours ( Cao-Lei et al, 2021 ; Jones et al, 2019 ).…”
Section: Introductionmentioning
confidence: 92%